PERCEIVED IMPORTANCE OF HEALTH DETERMINANTS AMONG LOWER LIMB AMPUTEES : INSIGHTS FROM A TERTIARY HOSPITAL IN MALAYSIA USING THE “MYSCORECARD” FRAMEWORK - Yew, Chung Khian; Chai, Chau Chung; Chung, Tze Yang (Wolters Kluwer Health, Inc., 2024)
OBJECTIVES: Lower limb amputation adversely affects the overall health and well-being of amputees. Prof. Dr. James Rimmer, head of the University of Alabama at Birmingham (UAB)/Lakeshore Research Collaborative introduced the comprehensive "MYSCORECARD," a holistic health management framework. “ MYSCORECARD ” comprise of three core domains (body, mind, and spirit),encompassing acronyms of eleven health determinants: "Minding your thoughts and emotions," "Your spiritual practice," "Self-care skills," "Core values," "Outdoor time in nature," "Relationships," "Exercise," "Contribution to others," "Arts and entertainment," "Rest and relaxation," and "Diet." This study aimed to identify important health determinants perceived by lower limb amputees and assess their fulfillment by using the "MYSCORECARD" framework.